PENGARUH STRATEGI BELAJAR MAJELIS TERHADAP PRESTASI BELAJAR IPS SISWA KELAS VIII SMP NEGERI 2 KUTA BARO ACEH BESAR - Eka Setia Waty; Husaini .; Nurasiah . (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2018)
ABSTRACT The study, entitled "The Effect of Assembly Learning Strategy on Student Achievement in Class IPS Subject VIII SMP Negeri 2 Kuta Baro Aceh Besar" aims to: (1) analyze the influence of learning strategy of the assembly on the learning achievement of IPS students of grade VIII SMP Negeri 2 Kuta Baro Aceh Besar; and (2) to explain the factors that influence student's learning achievement by using the learning strategy of the assemblies on the subjects of Social Studies Grade VIII SMP Negeri 2 Kuta Baro Aceh Besar. This research uses quantitative and qualitative approach and experimental research type. The population in this study were all students of class VIII SMP Negeri 2 Kuta Baro Aceh Besar which amounted to 65 people and consists of 3 classes, the sample used is class VIIIB consisting of 20 students as experimental class, and class VIIIA consisting of 20 students as control class. . Data collection techniques in this study using tests, interviews, and documentation. Based on the results of the research, it is known that (1) the homogeneity of the two sampled classes is homogeneous. This result can be known from homogeneity test result with calculation result Fhitung ≤ Ftable that is Fcount = 1,69 and Ftabel = 1,90 (2) for control class normality test obtained X2 count = 6,14 and X2tabel = 7,81 and in experiment class obtained X2hitung = 3.08 and X2tabel = 7.81 with the test criteria X2count ≤ X2table, then the control class and experiment class normal distribution (3) hypothesis test results using t-test and obtained t count = 3.14 and ttabel value at significant level α = 0,05 with dk = 38 is 2.04 with accepted criteria Ha if thitung ttable, in experiment class obtained the average value equal to 80,1 whereas in control class is got the mean value equal to 71, hence study strategy of assembly influential in improving students' learning achievement in the subjects of Social Studies Class VIII SMP Negeri 2 Kuta Baro Aceh Besar. Factors that affect student achievement by using the learning strategy of the assembly on the students of class VIII SMP Negeri 2 Kuta Baro Aceh Besar is the growing sense of curiosity of students on learning materials. Learning by using council strategies can improve students' learning motivation because students are directly involved actively organizing images and seeking information about the material they acquire. Keywords: Assembly Learning Strategy, IPS Learning Achievement.